The effect of English proficiency on the production of English intonation by Chinese EFL learners - Tian, Qingbo; Yap, Ngee Thai; Ng, Chwee Fang; Yahya, Yasir (Universiti Putra Malaysia, 2024)
English intonation is an integral component of English pronunciation teaching. However, as students’ proficiency levels in English pronunciation improve, it remains unclear whether their intonation levels also develop. The present study, based on the second language intonation learning theory, aims to investigate the influence of English proficiency on Chinese EFL learners’ production of English pitch accents, edge tones, and intonation patterns from the perspective of phonological representation. Two language groups of participants took part in a reading task: native English speakers (12) and Chinese EFL learners (36). The learners were classified into three groups based on their scores in the Chivox National Spoken English Test, ranked from high to low: the advanced, intermediate, and elementary groups. The reading task comprised 90 dialogue pairs. The participants were required to read part B of each dialogue pair aloud, but afterwards, only the Chinese EFL learners attended the semi-structured interview. The results showed that the native English speakers only demonstrated significant differences from each learner group in four of the ten intonation types involving the three aspects of English intonation, which may indicate regional variations in American English and difficulties distinguishing (H*) and (L+H*). In addition, there were no significant differences between the three learner groups in producing the ten intonation types, which maybe attributed to their similar learning experiences.